1999
DOI: 10.1128/mcb.19.9.6286
|View full text |Cite
|
Sign up to set email alerts
|

Insulin-Induced Phosphorylation and Activation of Cyclic Nucleotide Phosphodiesterase 3B by the Serine-Threonine Kinase Akt

Abstract: Cyclic nucleotide phosphodiesterase (PDE) is an important regulator of the cellular concentrations of the second messengers cyclic AMP (cAMP) and cGMP. Insulin activates the 3B isoform of PDE in adipocytes in a phosphoinositide 3-kinase-dependent manner; however, downstream effectors that mediate signaling to PDE3B remain unknown. Insulin-induced phosphorylation and activation of endogenous or recombinant PDE3B in 3T3-L1 adipocytes have now been shown to be inhibited by a dominant-negative mutant of the serine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
286
3
7

Year Published

2000
2000
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 341 publications
(307 citation statements)
references
References 47 publications
11
286
3
7
Order By: Relevance
“…Increased activity of PDE3B may cause rapid breakdown of cAMPs that are produced by GLP-1 activation (Härndahl et al, 2002). PDE3B is highly expressed in β-cells and can be activated by interaction with Akt (Ahmad et al, 2007;Kitamura et al, 1999). Indeed, our preliminary experiment showed that pretreatment of INS-1 cells with cilostamide, a specific inhibitor of PDE3B, significantly increased exe-4-induced cAMP accumulation and Erk phosphorylation (data not shown).…”
Section: Discussionmentioning
confidence: 72%
“…Increased activity of PDE3B may cause rapid breakdown of cAMPs that are produced by GLP-1 activation (Härndahl et al, 2002). PDE3B is highly expressed in β-cells and can be activated by interaction with Akt (Ahmad et al, 2007;Kitamura et al, 1999). Indeed, our preliminary experiment showed that pretreatment of INS-1 cells with cilostamide, a specific inhibitor of PDE3B, significantly increased exe-4-induced cAMP accumulation and Erk phosphorylation (data not shown).…”
Section: Discussionmentioning
confidence: 72%
“…In summary, these data suggest that PDE3B mediates the regulation of Ser 473 PKB phosphorylation. However, the opposite situation also appears to occur as PKB has previously been shown to regulate PDE3B phosphorylation and activation [16,35].…”
Section: Pde3b and Pde4mentioning
confidence: 99%
“…In adipocytes, PKB plays a crucial role in insulin-induced GLUT-4 translocation to the plasma membrane [14] and protein synthesis [15]. It also appears to be involved in the antilipolytic action of insulin through phosphorylation and activation of PDE3B [16,17].…”
Section: Introductionmentioning
confidence: 99%
“…Previous experiments have demonstrated that native RPDE3B was phosphorylated on serine 302 in intact rat adipocytes (analogous to serine 296 in MPDE3B) incubated with insulin (16), and that RPDE3B was also phosphorylated in vitro by partially purified rat adipocyte PKB (17) or rPKB (18). Available evidence suggests that phosphorylation is not required to maintain, but does increase, basal PDE activity.…”
Section: Effects Of Pkb On Phosphorylation/activation Of Pde3b In Vitromentioning
confidence: 99%
“…More recently, in oocytes (8), rat adipocytes (16,17), and 3T3-L1 adipocytes (18), PDE3 isoforms have been suggested to be downstream targets and effectors of PKB actions. In adipocytes, insulin-induced activation of PDE3B, via P13-K-and PKB-dependent signals, is a critical component in the antilipolytic action of insulin (19 -21).…”
Section: Cyclic Nucleotide Phosphodiesterase 3b Is a Downstream Targementioning
confidence: 99%